Answer:
When a triangle is translated, it means the triangle is moved away from its original position.
When the coordinates of a triangle, and the coordinate of only one point of the image are given, the translation rule is calculated by subtracting the coordinates of the pre-image from the image.
From the question, we understand that:
The vertices of the triangle are known. Assume they are:
\begin{gathered}A= (1,1)\\ B = (3,5) \\ C = (4,-1)\end{gathered}A=(1,1)B=(3,5)C=(4,−1)
The vertex of one of the image is also known. Assume the point is:
A' = (3,-1)A′=(3,−1)
To calculate the translation rule;
We simply subtract the vertices of the image from the pre-image.
In this case, the translation rule would be:
T < x,y > = A' - AT<x,y>=A′−A
So, we have:
T < x,y > = (3,-1) - (1,1)T<x,y>=(3,−1)−(1,1)
Rewrite as:
T < x,y > = (3 -1 ,-1 - 1)T<x,y>=(3−1,−1−1)
T < x,y > = (2 ,-2)T<x,y>=(2,−2)
So, the translation rule is:
T_{ < x,y > } (x,y) \to (x + 1, y - 1)T<x,y>(x,y)→(x+1,y−1)
Hence, the translation rule can be derived by subtracting the coordinates of the pre-image from the image.